Input Current Ripple Analysis of Multiphase PWM Inverters - Anwar Muqorobin; Pekik Argo Dahono (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper investigates the relationship between inverter phase number and inverter input current ripple. Analysis results show that increasing the phase number more than nine cannot provide significant input current ripple reduction. The input current ripple is not affected by the switching frequency. Simulation and experimental results are included in this paper to show the validity of the proposed analysis method.